1994
DOI: 10.1021/jm00043a013
|View full text |Cite
|
Sign up to set email alerts
|

substituted (S)-Phenylpiperidines and Rigid Congeners as Preferential Dopamine Autoreceptor Antagonists: Synthesis and Structure-Activity Relationships

Abstract: A series of (S)-phenylpiperidines in which the substituents on the aromatic ring and nitrogen have been varied has been prepared. They have been evaluated pharmacologically to explore the importance of these substituents for the interaction with central dopamine (DA) receptors. On the basis of biochemical and behavioral data in rats, several of these compounds are characterized as centrally acting DA autoreceptor antagonists. (S)-Phenylpiperidines having an aromatic substituent with a high group dipole moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 48 publications
2
90
1
Order By: Relevance
“…Thus, optimal treatment for these conditions may not rely solely on dopamine blockade but may also include a dopamine tone-dependent modulation or "stabilization" of the dopaminergic system. There is now a class of drugs that has been suggested to possess such properties, exemplified by (Ϫ)-OSU6162 and ACR16 (Sonesson et al, 1994;Ekesbo et al, 1997;Tedroff et al, 1998;Nichols et al, 2002;Carlsson et al, 2004;Nilsson et al, 2004;Rung et al, 2005). These compounds are reported to lack high in vitro affinity for various neuroreceptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, optimal treatment for these conditions may not rely solely on dopamine blockade but may also include a dopamine tone-dependent modulation or "stabilization" of the dopaminergic system. There is now a class of drugs that has been suggested to possess such properties, exemplified by (Ϫ)-OSU6162 and ACR16 (Sonesson et al, 1994;Ekesbo et al, 1997;Tedroff et al, 1998;Nichols et al, 2002;Carlsson et al, 2004;Nilsson et al, 2004;Rung et al, 2005). These compounds are reported to lack high in vitro affinity for various neuroreceptors.…”
mentioning
confidence: 99%
“…These compounds are reported to lack high in vitro affinity for various neuroreceptors. For (Ϫ)-OSU6162, D 2 and D 3 K i values were 447 and 1305, nM, respectively, and were reported with K i values Ͼ1 M for other targets (Sonesson et al, 1994), whereas for ACR16, the K i values for a number of targets, including monoaminergic receptors, were reported to be Ͼ10 M . Similar results were found by researchers at Eli Lilly with D 2 /D 3 K i values of 23/2.2 and 0.9/2.8 M for ACR16 and (Ϫ)-OSU6162, respectively, using 7-hydroxy-2-dipropylaminotetralin as radioligand in cloned cells transfected with human D 2 /D 3 receptors (S. Little, personal communication).…”
mentioning
confidence: 99%
“…This stabilizing concept was postulated based on a PET study in rhesus monkeys where infusions with the compound (-)-OSU6162 (OSU6162) induced a dopaminergic tone-dependent effect with a reduction in the striatal L-[11C]DOPA influx rate in monkeys with high baseline values and an increased striatal L-[11C]DOPA influx rate in animals with low baseline values [190]. The mechanism of action is, however, not completely understood, and although in vitro studies indicate that OSU6162, like aripiprazole, acts as a partial agonist at D2 receptors [191,192], behavioural studies have failed to demonstrate any intrinsic activity of the compound ( [195]). Instead it has been suggested that OSU6162 produces functionally opposite effects by acting as an antagonist at both presynaptic autoreceptors and postsynaptic D2 receptors [189,[193][194][195].…”
Section: Dopamine Stabilizersmentioning
confidence: 99%
“…The mechanism of action is, however, not completely understood, and although in vitro studies indicate that OSU6162, like aripiprazole, acts as a partial agonist at D2 receptors [191,192], behavioural studies have failed to demonstrate any intrinsic activity of the compound ( [195]). Instead it has been suggested that OSU6162 produces functionally opposite effects by acting as an antagonist at both presynaptic autoreceptors and postsynaptic D2 receptors [189,[193][194][195]. Based on the hypothesis that OSU6162 can counteract both hyper-and hypo-dopaminergic states, the compound has recently been evaluated in both animal models modulating alcohol-mediated behaviours as well as in a placebo-controlled human laboratory study in alcohol-dependent patients.…”
Section: Dopamine Stabilizersmentioning
confidence: 99%
“…79,80 They either exert a strong action on dopaminergic autoreceptors and/or they have a weaker effect postsynaptically, and/or they seem unable to reach a subpopulation of postsynaptic dopamine receptors. 81,82 The clinical significance of modulating, rather than simply decreasing or increasing DA transmission in the PFC, stems from the fact that cognitive symptoms have been associated with the finding that DA levels in the PFC should be maintained in a precise range in order to avoid functional impairment (see below). This has been shown in numerous diseases other than depression 83 or schizophrenia; 84 including Huntington's, 85 drug addiction, 86 and Parkinson's 87 as well as in normal aging.…”
Section: Modulation Of the Dopaminergic System: A Common Therapeutic mentioning
confidence: 99%